Titan Surface Temperatures during the Cassini Mission - Jennings, D. E.; Tokano, T.; Cottini, V; Nixon, C. A.; Achterberg, R. K.; Flasar, F. M.; Kunde, V. G.; Romani, P. N.; Samuelson, R. E.; Segura, M. E.; Gorius, N. J. P.; Guandique, E.; et al. (IOP PUBLISHING LTD, 2019)
By the close of the Cassini mission in 2017 the Composite Infrared Spectrometer had recorded surface brightness temperatures on Titan for 13 yr (almost half a Titan year). We mapped temperatures in latitude from pole to pole in seven time segments from northern mid-winter to northern summer solstice. At the beginning of the mission the warmest temperatures were centered at 13 S where they peaked at 93.9 K. Temperatures fell off by about 4 K toward the north pole and 2 K toward the south pole. As the seasons progressed the warmest temperatures shifted northward, tracking the subsolar point, and at northern summer solstice were centered at 24 N. While moving north the peak temperature decreased by about 1 K, reaching 92.8 K at solstice. At solstice the fall-off toward the north and south poles were 1 K and 3 K, respectively. Thus the temperature range was the same 2 K at the two poles. Our observed surface temperatures agree with recent general circulation model results that take account of methane hydrology and imply that hemispherical differences in Titan's topography may play a role in the north-south asymmetry on Titan.